How galling herbivores share a single super-host plant during their phenological cycle: the case of Mimosa gemmulata Barneby (Fabaceae) - Costa, Elaine C.; Martini, Vitor C.; Souza-Silva, Aline; Lemos-Filho, José P.; Oliveira, Denis C.; Isaias, Rosy M. S. (Tropical ecology, 2022)
The success of the galling insects sharing the same microhabitat depends both on the synchrony of their life cycles with the leaf flushing of the super-host plant and to the asynchrony among their life cycles. The asynchrony of the multivoltine life cycles of Lopesia spp. (Diptera—Cecidomyiidae) is favored by the constant leaf flushing in M. gemmulata, and favors the non-overlapping of gall induction periods. Peculiarly, the univoltine life cycle of the galling Lepidoptera on its stem galls is synchronized to the availability of mature host leaves during the rainy season, which is important for the water potential in host stem branches. The abundance of the Lopesia gall morphotypes follow the phenology of M. gemmulata, which obeys the seasonal pattern of water availability in the neotropical savanna climate.